Intensive Pig Farming with Improved Breed A profitable enterprise for unemployed youth - Chandra, Ramesh; Chatlod, L R; Kumar, Santosh (Indian Farming, 2018)
Farmers rear pig in a traditional system. However, there is an ample scope to use pig production as economic changer of unemployed youth by introducing improved animal husbandry practices, good germplasm, feeding, health control measures and breeding strategies.